The Influence of Technology Acceptance Model (TAM) on The Intention to Use Online Check-in System at Hotels (Journal of Innovation, Business and Entrepreneurship, 2020)
Online check-in for hotels is a system designed to handle hotel guests, which allows guests to verify data online to make the check-in process more effective and efficient. This technology system has not been implemented in Indonesia. However, it has the potential for development to be implemented in hotels in Indonesia. This study focuses on online check-in systems as a specialized area in the hospitality industry. The implementation of this system makes the check-in process much more effective and efficient. This study analyzes the factors that influence the intention to use an online check-in system in the hospitality industry in Indonesia using an analysis of the Technology Acceptance Model (TAM). The results show that the independent variables Perceived Easy to Use and Perceived Usefulness have a positive influence on the intention to use the online check-in system at hotels. This study provides insight related to the role of technology acceptance models that affect the intention to use the online check-in system to be used by companies in determining marketing strategies.Keywords: online check-in system, hotel, Perceived Easy to Use, Perceived Usefulness, Intention to Use